Absorption, Distribution, and Excretion of the Investigational Agent Orteronel (TAK-700) in Healthy Male Subjects: A Phase 1, Open-Label, Single-Dose Study - Suri, Ajit; Pusalkar, Sandeepraj; Li, Yuexian; Prakash, Shimoga (Clinical pharmacology in drug development, 2016)
This study evaluated the absorption, distribution, and excretion of orteronel, an investigational, nonsteroidal, reversible, selective 17,20‐lyase inhibitor. Six healthy male subjects received a single 400‐mg dose of radiolabeled [14C]‐orteronel (18.5 kBq). The pharmacokinetics of [14C]‐radioactivity, orteronel, and the primary metabolite M‐I were characterized by ultra‐performance liquid chromatography–tandem mass spectrometry, and mass balance recovery of [14C]‐radioactivity was determined by liquid scintillation counting and accelerator mass spectrometry. Median time to maximum observed concentration of [14C]‐radioactivity was 2.5 hours (plasma/whole blood) and of orteronel was 1 hour (plasma). Mean terminal half‐life for [14C]‐radioactivity in plasma and whole blood was 9.46 and 7.39 hours, respectively. For [14C]‐radioactivity, the geometric mean whole blood–to–plasma ratios for maximum observed plasma/whole‐blood concentration, area under the plasma concentration–time curve from time 0 to last quantifiable concentration (AUC0–last), and AUC0–inf (AUC from time 0 to infinity) were 1.04, 0.92, and 0.93, respectively. Dose recovery accounted for 95.9% of the administered orteronel dose; the majority of excretion occurred by 96 hours postdose. The principal excretion route was via urine (mean, 77.5%; including 49.7% unchanged drug and 16.3% M‐I) compared with 18.4% via feces. Three mild adverse events were reported; none were considered serious or related to orteronel.